Common Traits Spark the Mitophagy/Xenophagy Interplay - Singh, Aarti; Kendall, Sharon L.; Campanella, Michelangelo (Frontiers in Physiology, 2018)
Autophagy contributes to the wellbeing of eukaryotic cells by recycling cellular components, disposing damaged organelles and removing pathogens. Both the quality control process of selective mitochondrial autophagy (Mitophagy) and the defensive process one of intracellular pathogen-engulfment (Xenophagy) are facilitated via protein assemblies which have shared molecules, a prime example being the Tank-Binding Kinase (TBK)1. TBK1 plays a central role in the immunity response driven by Xenophagy and was recently shown to be an amplifying mechanism in Mitophagy, bring to attention the potential cross-talk between the two processes. Here we draw parallels between Xenophagy and Mitophagy, speculating on the inhibitory mechanisms of specific proteins (e.g. the 18kDa protein TSPO), how the preferential sequestering towards one of the two pathways may undermine the other, and in this way impair cellular response to pathogens and cellular immunity. We believe that an in depth understanding of the commonalities may present an opportunity to design novel therapeutic strategies targeted at both the autonomous and non-autonomous processes of selective autophagy.